Protective roles of ginseng against bacterial infection - Ye-Ram Kim; Chul-Su Yang (Microbial Cell)
Ginseng (Panax ginseng Meyer) is a well-known traditional herbal medicine that plays a protective role against microbial attack. Several studies have revealed its anti-cancer, anti-inflammatory, and immune-modulatory effects. Ginseng contains several components that vary according to the year of cultivation and the processing method used, such as heating, drying, and steaming, which induce different degrees of pharmacological activities. This review discusses the antibacterial effects of ginseng against pathogenic bacterial infections. We describe how ginseng regulates pathogenic factors that are harmful to the host and discuss the therapeutic potential of ginseng as a natural antibacterial drug to combat bacterial infectious disease, which is a global public health challenge. The components of ginseng could be novel alternatives to solve the growing problem of antibiotic resistance and toxicity.